ANALISIS SIFAT MEKANIK ALAT PENGUPAS KELAPA TRADISIONAL DENGAN VARIASI LAJU PENDINGINAN - Jailani Aqj; Fentje Abdul Rauf; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
This research aim to determine the analyze differences of mechanical properties of coconut peeler material at varying cooling rate. Basic material of coconut peeler in the research is spring steel car.The result of the experiment showed that without cooling treatment, the level is 382,972 N/ð‘šð‘š2, for the care of cooling specimen at varying cooling rate, the highest level is 628,986 N/ð‘šð‘š2. The largest impact level is about absorb 0,37 J/mmÂ² which absorption energy around obtainable at the lowest cooling rate.Keywords : Coconut Peeler, Mechanical Properties, Conditioning Rate.